SARS‐CoV‐2 targets neurons of 3D human brain organoids - Ramani, Anand; Müller, Lisa; Ostermann, Philipp N; Gabriel, Elke; Abida‐Islam, Pranty; Müller‐Schiffmann, Andreas; Mariappan, Aruljothi; Goureau, Olivier; Gruell, Henning; Walker, Andreas; Andrée, Marcel; Hauka, Sandra; et al. (The EMBO journal, 2020)
COVID‐19 pandemic caused by SARS‐CoV‐2 infection is a public health emergency. COVID‐19 typically exhibits respiratory illness. Unexpectedly, emerging clinical reports indicate that neurological symptoms continue to rise, suggesting detrimental effects of SARS‐CoV‐2 on the central nervous system (CNS). Here, we show that a Düsseldorf isolate of SARS‐CoV‐2 enters 3D human brain organoids within 2 days of exposure. We identified that SARS‐CoV‐2 preferably targets neurons of brain organoids. Imaging neurons of organoids reveal that SARS‐CoV‐2 exposure is associated with altered distribution of Tau from axons to soma, hyperphosphorylation, and apparent neuronal death. Our studies, therefore, provide initial insights into the potential neurotoxic effect of SARS‐CoV‐2 and emphasize that brain organoids could model CNS pathologies of COVID‐19. Synopsis Modelling coronavirus exposure of the central nervous system is critical to assess the cellular tropism and potential neurological consequences of infection. Here, a Düsseldorf isolate of SARS‐CoV‐2 is shown to enter human cerebral organoids and preferably target neuronal cells. Clinical SARS‐CoV-2 strain targets neurons of 3D human brain organoids. SARS‐CoV-2 does not appear to actively proliferate in neurons. SARS‐CoV-2 is associated with Tau abnormalities in neurons. SARS‐CoV-2 induces neuronal cell death. Graphical Abstract In vitro exposure of cerebral organoids to coronavirus results in preferential infection and cell death of neuronal cells.